Teachers’ Preparations for Implementing Mother Tongue-Based Multilingual Education in Teaching English (Studies in ELT and Applied Linguistics, 2025)
Mother tongue-based multilingual education (MTB-MLE) in Nepal is a suitable and beneficial approach for students from indigenous language groups to learn English from their early grades. Teaching English through students' mother tongues helps them not only acquire English effectively but also understand subject matter more comprehensively. MTB-MLE integrates students’ mother tongues into English education, enabling them to transfer knowledge, skills, learning methods, and experiences through their native languages to additional ones, fostering sustainable learning outcomes at the basic education level. This study aims to explore teachers’ competencies in terms of pedagogical, curriculum, content, and methodological knowledge within MTB-MLE-implemented classrooms. It relies on secondary materials, including journals, books, and reports, which are reviewed and analyzed against relevant literature. The findings reveal that teachers’ competencies significantly contribute to their professional growth and development, emphasizing the importance of theoretical and practical knowledge for effective English teaching in multilingual classroom settings.